Answer:
![-(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/g3dzahzg2weqewvw38ee4amnmv0vijzmvk.png)
Explanation:
1. Multiply both sides of the equation by the LCM (x - 2)(x + 2):
![(2)/(x^(2) -4) (x-2)(x+2)](https://img.qammunity.org/2023/formulas/mathematics/college/kbxhek19kjjmvk5iesgt721d0emycczhec.png)
factor x² - 4 by rewriting it as x² - 2²
x² - 2² = (x + 2)(x - 2)
now we have;
![(2)/((x+2)(x-2)) (x-2)(x+2)](https://img.qammunity.org/2023/formulas/mathematics/college/pqn67q111z44kexej15ny4j8yt5h9jrtyz.png)
cancel the common factors (x - 2)(x + 2)
= 2
-------------------------------
![(-1)/(x+2) (x-2)(x+2)](https://img.qammunity.org/2023/formulas/mathematics/college/ayd9124da5tt8liv6wkazltj6ht3titzve.png)
cross cancel the common factor (x + 2)
![(-1)/(x-2)=-(x-2)=-x+2](https://img.qammunity.org/2023/formulas/mathematics/college/3tciq01fz6kuvts7h20u5wswr7j2nadgm1.png)
-------------------------------
![(3)/(x-2) (x-2)(x+2)](https://img.qammunity.org/2023/formulas/mathematics/college/4mfawslp3dby3k9udmkycchxlrx6cq9unz.png)
cross cancel the common factor (x - 2)
3(x + 2)
distribute the 3
3x + 6
-------------------------------
combining all new values, we have;
2 + (-x) + 2 = 3x + 6
-x + 4 = 3x + 6
2. Isolate x:
-x + 4-4 = 3x + 6-4
-x = 3x + 2
-x-3x = 3x-3x + 2
-4x = 2
-4x/-4 = 2/-4
x =
![-(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/g3dzahzg2weqewvw38ee4amnmv0vijzmvk.png)
hope this helps!